THE ROLE OF COHESIVE DEVICES AS TEXTUAL CONSTRAINTS ON RELEVANCE: A DISCOURSE-AS-PROCESS VIEW - Moreno, Ana L. (International Journal of English Studies, 2003)
Drawing on Relevance Theory (Sperber and Wilson, 1986; Blakemore, 1987, 1992) and taking insights from Sinclair's (1993) model of written text structure, the purpose of this paper is toshow how and which cohesive features play an important role in helping the reader perceive relevance and coherence when a text is approached in the process of reading. With this aim, a comment article from Guurdiun UnIinzited consisting of 60 coherence units is analyzed by a group of 25 subjects. The study seeks to capture the coherence pattem perceived by a discourse community rather than by an individual researcher. The results show that in most cases the cohesive resources that contribute to the perception of the discourse relevance and coherence of this text at each juncture deal only with discourse meaning derived from whole sentences, larger fragments of text, or occasionally, certain simple clauses linked paratactically, and they do much more than effect a tenuous connection between isolated constituents of sentences.